Preliminary Experiments to Evaluate the Relative Efficiency of Different natural Baits in Line Fishing - Balasubramanyan, R (Fishery Technology, 1964)
A series of experimental hand-line fishing operations were conducted off the Madras coast employing five different types of natural fish baits. Based on the total catch of fish per day of fishing under each type of bait used, a comparative study on the catching efficiency of the different natural fish-baits were made. The reaction of the fish to a particular bait appears to be the result of a complex process. Live baits have the maximum catching efficiency as seen from the fish landings when live prawns were employed as a bait. The procurement of live baitsis a serious problem to the fishermen and as such suitable artificial fish lures can be profitably employed.